Caladium cv. Florida sweetheart production at different planting depths and sowing dates - Hussain, Ibrar; Ul Amin, Noor (Ornamental Horticulture, 2018)
Ornamental bulbous crops emergence and yield can be improved by its emergence from soil. The response of Caladium to different planting depths and dates was investigated at Ornamental Horticulture Nursery, Department of Horticulture, The University of Agriculture, Peshawar during the year 2008. Randomized Complete Block Design in a split plot arrangement was used repeated three times. Sowing dates (30th March, 15th April and 30th April) were allotted to main plots whereas planting depths (2.5 cm, 5 cm, 7.5 cm and 10 cm) were kept in sub plots. Findings revealed that Caladium tubers sown on 30th March took maximum days to sprouting (33), produced maximum number of sprouts plant-1 (2.21), gained maximum tuber size (40.88 cm3) with high tuber yield (5397 kg ha-1). On the other hand, tubers sown on 30th April took less days to sprouting (20.21), produced less number of sprouts plant-1(1.53), produced small tuber (33.28 cm3) and total tuber yields was also less (4374 kg ha-1). In case of planting depth, Caladium tubers sown at a depth of 7.5cm resulted in maximum plant height (52 cm), tuber size (41.76 cm3), and tuber yield (5288 kg ha-1) while maximum number of tubers plant-1 (1.92) was observed at a depth of 10 cm. Tubers sown in 2.5 cm depth resulted in minimum tuber yield (4538 kg ha-1) and plant height (46.56 cm). To maximize vegetative as well as tubers production of Caladium cv. Florida sweet heart, it shall be sown on 30th March with 7.5cm depth.